Admixture history of the South African "Coloured" populations - Daniels, RJ (2019)
Admixed people formed from colonial era migrations are a major feature of present-day diversity. In Southern Africa, establishment of the Dutch Cape Colony instigated the so-called "Coloured" communities, associated, essentialistically, with 'mixed descent'. This multi-way admixture involved diverse regional groups producing a fascinating genetic story. In this thesis I develop further the history of the Cape Colony admixture using genome-wide SNP chip data.